Recurrent complex ameloblastoma of infratemporal fossa in a young adult: a challenging case report - Aregala, Praneeth; Marda, Sachin; Gowda, Sreehari; Pullikanti, Bhulaxmi; Jyoshna, T. M. (International Surgery Journal, 2025)
An uncommon, histologically benign, but aggressive, tumor of the jaws, ameloblastoma develops from odontogenic epithelium and has the capacity to extensively destroy jaw bones and infiltrate surrounding tissues. After incomplete treatment, recurrences are frequent. The orbit, anterior cerebral cavity, temporal and infratemporal fossa, and other challenging locations can experience recurrences. We report a case of recurrent complex cystic ameloblastoma over the right side of the face in a 31-year-old gentleman who presented with right facial swelling, serous discharge, intermittent pain, and decreased mouth opening for 2 years. Computed tomography (CT) head and neck with 3D reconstruction showed a complex solid-cystic multiloculated mass lesion in the right infratemporal fossa with large cystic components, septations, solid enhancing components, and peripheral calcifications, closely abutting the parotid gland, pterygoids, mandible, and maxillary antrum. Needful evaluation done. The patient underwent wide local excision of the tumor, right infrastructure maxillectomy, superficial parotidectomy, modified radical neck dissection, and microvascular alanine aminotransferase (ALT) free flap reconstruction. Complete surgical resection with negative margins is the hallmark for curative resection. Local recurrences are rare and usually amenable to re-resection. Postoperative radiotherapy for patients at increased risk of local recurrence improves local tumor control.